New geographical records and key to the species of Eumerus Meigen, 1823 (Diptera, Syrphidae) introduced into the Americas and Hawaii - Garcete-Barrett,Bolívar R. (2020)
Abstract Eumerus Meigen, 1823 is a very speciose genus of flower flies from the Eastern Hemisphere. Several reports of introduced species of this genus in the Americas have been recorded since early in the twentieth century, with a present list of six species recorded to date from the Americas and the US territory of Hawaii. In this paper we give new geographical records for the African-native species Eumerus obliquus (Fabricius, 1805), which reflect the expansion of this fly through Brazil and Paraguay along the last twenty years. At the same time, we report a second species from Paraguay, Eumerus aurifrons (Wiedemann, 1824), being this the first Western Hemisphere record for this Asian-native species. We finally provide an identification key to all of the species of Eumerus presently known from the Americas and Hawaii.